Discussion about „Encyclopaedic dictionary of education science" by L. Jovaiša - Targamadzė, Vilija (Acta Paedagogica Vilnensia, 2007)
A review of the “Encyclopaedic dictionary of education science" by Leonas Jovaiša
Keywords: educational science; dictionary; L. Jovaiša